Fascinating Sungai Petani: the influence of youth and social media - Mohd Yusof, Noorlailahusna; Azizan, Intan Syahriza; Ahmad, Nor Ardyanti; Ismail, Junaida; Yusoff, Siti Norfazlina (Universiti Teknologi MARA, Kedah, 2024)
This article aims to examine youth’s participation in promoting local tourism activities using social media. The preference for using social media as a digital platform to promote local tourism activities has a significant impact on the economic, social, and cultural. The main aim of this study is to understand how social media is effective in reaching and communicating with potential audiences and examine whether the social media platforms used by youth to promote local tourism activities are successful or not. We used a quantitative method over 30 days to track the number of times viewers watched, liked, shared, and commented on an advertising video. The main findings show a high level of viewer involvement, as seen by the quantity of views, likes, shares, and comments. The findings also indicate that youth roles are important in using social media to promote local tourism activities and participation. By improving the visibility of local communities, this study aims to increase the number of tourists to Sungai Petani and concurrently improve the standard of living of local communities. We concluded that youth, using social media, play important roles as social agents in promoting local tourism activities in local communities.